Asystole kidney donation using automated chest compression system and hypothermic oxygenated machine perfusion (first experience in the Russian Federation) - A. V. Shabunin; M. G. Minina; P. A. Drozdov; V. M. Sevostianov; I. V. Nesterenko; D. A. Makeev; O. S. Zhuravel (Вестник трансплантологии и искусственных органов)
Objective: to demonstrate, using a clinical case, the first successful experience in a combined use of an automated chest compression device (ACCD) and hypothermic oxygenated machine perfusion (HOPE) for kidney transplantation from a donor with irreversible cardiopulmonary arrest. Materials and methods. In the presented clinical case, ACCD was successfully used in a donor who was pronounced dead following an irreversible cardiopulmonary arrest. This allowed to minimize the primary warm ischemia time. Kidney graft HOPE for 585 minutes reduced the static cold storage time to 165 minutes. Results. In the uneventful postoperative period, there was immediate kidney graft function. This allowed for rapid rehabilitation and discharge from hospital. Conclusion. Introduction of ACCD and HOPE will increase the number of donor organs, mainly kidneys intended for transplantation.